Ukuran Perusahaan Struktur Modal dan Nilai Perusahaaan - Wokas, Heince R.N (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2014)
The objective of this study is to find and to test the effect of firm size, capital structure, to firm value.Â  The data for this study is secondary and taken in period of 2009 till 2011. The background of this study is based on inconsistency between fir size and capital structure to firm value. The study is using 22 listed companies in Indonesia Stock Exchange. This study is conducting path analysis for hypothesis testing. The result of analysis is showing that firm size is not affecting the capital structure. Because market consideration on entity is to see the performance of entity to empower their internal funding rather than its size. This study is showing the significance relationship between capital structure and firm value of manufacturer companies in Indonesia.